South China Sea : energy and security conflicts - Daniels, Christopher L., 1982- (Global flashpoints., 2014)
South China Sea: Energy and Security Conflicts takes on such troubling questions as the impact of this conflict on global oil and gas prices; China's growth both economically and as a regional military hegemon; and the recent, often rocky, international efforts to mediate the conflict. In addition to policy recommendations for peaceful resolutions to this emerging international challenge, the book includes maps, graphs, primary sources, and overviews of key players-individual and institutional-in what may well be the next great conflict in.